A framework for Assessing Translation among Multiple Representations - Andriani, Parhaini; Kurniawati, Kiki Riska Ayu; Afriyani, Dona (Universitas Muhammadiyah Mataram, 2022)
Translation among multiple representations is one of the important abilities to be possessed by prospective mathematics teachers. The mathematics learning curriculum ranging from elementary to college level needs to emphasize the ability to translate mathematical ideas in a form of representation to different mathematical representation structures. Assessing of this ability is important because it can be used as a basis for developing other mathematical literacy skills. The purpose of this study is to describe the level of translation between mathematical representations of prospective mathematics teachers. A descriptive qualitative study was conducted to fourty prospective mathematics teachers in State Islamic University of Mataram. The selection of research subjects was carried out in a purposive sampling. Data were obtained from mathematical translational thinking task in the form of an assignment sheet consisting of 2 questions related to quadratic equations and task-based interviews. Data were analyzed using fixed comparison analysis, which is comparing incidents (phenomena) with the aim of classifying data. The study found five levels of translational ability between mathematical representations, which were named: level 0, level 1, level 2, level 3 and level 4. The characteristics of each level are built based on four mathematical translational thinking processes: unpacking the source of representations, coordinating initial stage, design the target representation and determine the equivalence between the source and target representations. The findings in this study could be used as a guide to develop an instrument to assess mathematical translation ability.